Dampak upah minimum, IPM, dan partisipasi angkatan kerja terhadap pengangguran: Analisis data panel lima kabupaten Jawa Tengah - Salsabila , ‘Ainun Hanum; Rahmatillah, Agisva Elvatikha; Arwansa, Damai; Mukharohmah, Maulia Siti; Septiani, Yustirania (Nur Science Institute, 2025)
This study examines the factors influencing the open unemployment rate in five regencies—Brebes, Cilacap, Tegal, Pemalang, and Banyumas—during 2017–2023. These regions were selected due to their consistently higher unemployment rates than the national average. The variables analyzed include the Regency Minimum Wage, Human Development Index (HDI), and Labor Force Participation Rate (LFPR). The Random Effects Model (REM) conducted a panel data regression analysis. The results show that the minimum wage significantly affects the open unemployment rate, while HDI and LFPR have significant adverse effects. These variables explain a substantial portion of unemployment variation across the selected regencies. The findings suggest that policymakers should balance wage regulations, increase investment in education and health, and promote industrial development to support job creation. The results provide empirical insights to assist local governments, labor agencies, and other stakeholders in formulating evidence-based employment policies.